State of the art of the "virtual" concept in the world and in Latin America - Alfonso Soriano Espinosa (Corporación Universitaria Minuto de Dios, 2009)
The purpose of this paper is to provide a basic but thorough overview of the main references that have approached the concept virtual reality and other concepts belonging to the cybercultural studies, such as those of cyberspace, culture and communication. It also presents a roadmap for the development of cybercultural studies in Latin America, to the extent that there has been a lack of consistency in the Latin American views on the subject that have been carried out so far.